ANALISIS PENGANGGURAN DI INDONESIA BAGIAN BARAT - Lailan Syafrina Hasibuan; Nursalamah Nursalamah (KOLONI, 2022)
Indonesia is part of the Association of Southeast Asian Nations and Group of Twenty and participates in carrying out sustainable economic development. However, macroeconomic developments are still experiencing problems with employment, resulting in unemployment. Unemployment is a very serious problem because it involves people's welfare which in turn results in disruption of social and political stability. So the purpose of this study is to determine the effect of HDI, inflation and economic growth on unemployment in Western Indonesia during the 2014-2019 period. This study uses a quantitative approach with panel data regression. This research was conducted in 18 provinces in western Indonesia with a total of 108 observations. Based on the results of the Chow test and Hausman test, the correct parameter estimation method used in this study is the Fixed Effect Model (FEM). The results of the Fixed Effect Model (FEM) show that individually the HDI, inflation and economic growth variables have a negative and significant effect on unemployment in western Indonesia. Keywords: Unemployment, HDI, Inflation, Economic Growth.